Teaching & learning in line with MQF2024: preparing future-ready graduates - Ismail, Norul Fadhilah; Ramli, Intan Syaherra (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The Malaysian Qualifications Framework 2024 (MQF 2024) represents an important step in higher education reform by aligning academic standards with global benchmarks while maintaining local relevance. The framework promotes a holistic teaching and learning approach that develops intellectual ability, ethical values, employability skills, and adaptability to technological changes, forming the foundation for future educational practices.